Contributors - Christian Ulrik Andersen (A Peer-Reviewed Journal About, 2023)
Camille Crichlow is a PhD Researcher at the Sarah Parker Remond Centre for the Study of Racism and Racialisation (University College London). Her research interrogates how the historical and socio-cultural narrative of race manifests in contemporary algorithmic technologies.